Clinical characteristics of human immunodeficiency virus patients being referred for liver transplant evaluation: a descriptive cohort study. Issue 4 (15th June 2015) - Martel‐Laferrière, V.; Michel, A.; Schaefer, S.; Bindal, S.; Bichoupan, K.; Branch, A.D.; Huprikar, S.; Schiano, T.D.; Perumalswami, P.V.
Abstract Background Liver transplantation (LT) is a treatment option for select human immunodeficiency virus (HIV)‐infected patients with advanced liver disease. The aim of this study was to describe LT evaluation outcomes in HIV‐infected patients. Methods All HIV‐infected patients referred for their first LT evaluation at the Mount Sinai Medical Center were included in this retrospective, descriptive cohort study. Multivariable logistic regression was used to identify factors independently associated with listing. Results Between February 2000 and April 2012, 366 patients were evaluated for LT, with 66 (18.0%) listed for LT and 300 (82.0%) not listed. Fifty‐one patients (13.9%) died before completing evaluation and 85 (23.2%) were too early for listing. Reasons patients were declined for listing were psychosocial (15.8%), HIV‐related (10.4%), loss to follow‐up (9.6%), surgical/medical (6.0%), liver‐related (4.4%), patient choice (3.4%), and financial (1.6%). Listed patients were more likely to have hepatocellular carcinoma (HCC) (43.1% vs. 17.1%; P < 0.0001) and less likely to have hepatitis B (6.2% vs. 15.7%; P = 0.04) or a psychiatric history (19.7% vs. 35.2%; P = 0.02) than those not listed. In multivariable analysis, HCC (odds ratio [OR] 5.79; 95% confidence interval [95% CI]: 2.97–11.28), model for end‐stage liver disease (MELD) score at referral (OR 1.06; 95% CI 1.01–1.11), and hepatitis B (OR 0.26; 95% CI 0.08–0.79) were associated with listing. Conclusion MELD score and HCC were positive predictors of listing in HIV‐infected patients referred for LT evaluation and, therefore, timely referrals are vital in these patients. As MELD is a predictor for death while undergoing evaluation, rapid evaluation should be performed in HIV‐infected patients with a higher MELD score.